2023
DOI: 10.3390/genes14010197
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Prediction of Long Non-Coding RNA in Longissimus Dorsi Muscle of Queshan Black and Large White Pigs

Abstract: Long non-coding RNA (lncRNA) participates in the regulation of various biological processes, but its function and characteristics in intramuscular fat (IMF) deposition in different breeds of pigs have not been fully understood. IMF content is one of the important factors affecting pork quality. In the present study, the differentially expressed lncRNAs (DE lncRNAs) and their target genes were screened by comparing Queshan Black (QS) and Large White (LW) pigs based on RNA-seq. The results displayed 55 DE lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Specifically, in adipose tissue, we found that the SOX5 , ENSSSCG00000014414 , PPP1R12A , ZNF148 , TNFSF10 , and ROCK1 genes were under selection in Eastern pigs and significantly upregulated in adipose tissue, suggesting their potential influence on adipose deposition. Moreover, previous research has shown that SOX5 , PPP1R12A , ZNF148 , TNFSF10 , and ROCK1 genes regulate adipose deposition processes [ 54 , 55 , 56 , 57 , 58 , 59 ]. In blood, the MACF1 , IL1RL1 , MGA , TTC14 , ANKRD17 , PDLIM7 , FGD3 , NPRL3 , ENSSSCG00000014060 , ENSSSCG00000039214 , CYB5A , and HAGH genes were under selection in Eastern pigs, and the MACF1 , IL1RL1 , MGA , TTC14 , and ANKRD17 genes were significantly upregulated in Eastern pig blood.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in adipose tissue, we found that the SOX5 , ENSSSCG00000014414 , PPP1R12A , ZNF148 , TNFSF10 , and ROCK1 genes were under selection in Eastern pigs and significantly upregulated in adipose tissue, suggesting their potential influence on adipose deposition. Moreover, previous research has shown that SOX5 , PPP1R12A , ZNF148 , TNFSF10 , and ROCK1 genes regulate adipose deposition processes [ 54 , 55 , 56 , 57 , 58 , 59 ]. In blood, the MACF1 , IL1RL1 , MGA , TTC14 , ANKRD17 , PDLIM7 , FGD3 , NPRL3 , ENSSSCG00000014060 , ENSSSCG00000039214 , CYB5A , and HAGH genes were under selection in Eastern pigs, and the MACF1 , IL1RL1 , MGA , TTC14 , and ANKRD17 genes were significantly upregulated in Eastern pig blood.…”
Section: Discussionmentioning
confidence: 99%
“…Sample Collection, Sequencing, and m6A-circRNA Prediction Analysis Sample collection was described previously. Briefly, the experimental animals were three Queshan Black and three Large White pigs, all of which were castrated boars in this study, and samples were frozen in liquid nitrogen and stored at −80 • C until RNA extraction [17,18]. Total RNA was extracted from the samples using TRIzol reagent (15596026, Thermo Fisher Scientific, Waltham, MA, USA), and its concentration and quality were tested for satisfactory sequencing analysis.…”
Section: Methodsmentioning
confidence: 99%